State-space feedback controllers and PID controller implementation for a DC motor with two masses using dSPACE (MASKAY, 2017)
This article presents the design and implementation of two state feedback controllers, and a proportional integral derivative controller PID is applied to a DC motor with a coupled mass on its axis and a second mass connected by a band. The variable to be controlled is the angular position of the DC motor. This article summarizes the design, implementation, and functional tests of three controllers, which have been implemented and tested on the same hardware but with different requirements for the angular position amplitude of the DC motor. The controllers' operation tests have been made on the physical motor with two masses and on the mathematical model of the electromechanical system, which allows a comparison of the controller running on the hardware and the simulated system. Each controller has been designed to obtain the shortest settling time for the step function response.
Keywords: State variable feedback controller; DC motor; Proportional integral derivative controller